PRETREATMENT MINYAK JELANTAH DENGAN MENGGUNAKAN ADSORBEN SEBAGAI BAHAN BAKU BIODIESEL - Trisnaliany, Lety (Politeknik Negeri Sriwijaya, 2019)
This research is about recycling processed cooking oil into oil which can be used as raw material of biodiesel in a clean condition without dirt and low FFA, by using bagasse and banana peel as natural absorbent material and bleaching earth or pale soil as a chemical absorbent. Natural absorbent materials such as bagasse as well as banana peels that have been used as adsorbents can be directly used to absorb waste of waste oil into raw materials of biodiesel. From the result of the research, we found that the weight of adsorbent of optimum bagasse at SNI is 13% with free fatty acid 0.49%, acid number 0.37 mg KOH/mg Sample, number of sapling 187 and water content 0.43%. As well as the weight of the optimal banana husk adsorbent according to the SNI is 13% with free fatty acid 0.63%, the acid number 0.45 mg KOH/mg samples, the rate of sapding 135.58 and the moisture content of 0.43%. This indicates that the purifying tool jelantah oil by utilizing adsorbent of bagasse and banana peel skin as comparator to produce biodiesel raw material according to SNI. Whereas for chemical adsorbents, the results showed that the optimum conditions were obtained at 25% concentration and 60 minutes. For adsorbent 25% of free fatty acid acquisition was 0.49%, acidic value was 0.37, saponification number was 187 and water content was 0.018%. Where this number has produced biodiesel raw materials according to SNI.